2023
DOI: 10.3389/fnut.2023.1263853
|View full text |Cite
|
Sign up to set email alerts
|

Selenium intake and multiple health-related outcomes: an umbrella review of meta-analyses

Puze Wang,
Bo Chen,
Yin Huang
et al.

Abstract: Selenium is an essential trace metalloid element that is associated with fundamental importance to human health. Our umbrella review aimed to evaluate the quality of evidence, validity, and biases in the relationship between selenium intake and health-related outcomes according to published systematic reviews with pooled data and meta-analyses. Selenium intake is associated with a decreased risk of digestive system cancers, all-cause mortality, depression, and Keshan disease, when in children reduce the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been recommended that people with serum or plasma selenium concentration of at least 122 μg/L should not supplement selenium as this may increase the risk of adverse events, including cancer and type 2 diabetes. 7 , 81 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been recommended that people with serum or plasma selenium concentration of at least 122 μg/L should not supplement selenium as this may increase the risk of adverse events, including cancer and type 2 diabetes. 7 , 81 …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the differences in baseline characteristics among the participants included in different studies. Additionally, other studies have found that dietary selenium plays a role in preventing cancer incidence, especially colorectal cancer, prostatic cancer, and non-melanoma skin cancer ( 37–39 ). At present, some selenium-based compounds or selenium derivatives have shown excellent anticancer activity in experiments ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The trace element Se is crucial and widely distributed across the Earth’s atmosphere, lithosphere, and hydrosphere. The predominant forms of Se in the natural environment are inorganic compounds, including selenite, selenide, and selenate ( 45 ). Moreover, Se is an indispensable trace element for the human body, exhibiting diverse biological functionalities.…”
Section: Selenium and Kashin-beck Diseasementioning
confidence: 99%